The Request Strategies Used By The Students Of SMP N 3 Pati Grade IX Academic Year 2012/ 2013 - Susilo, Welas Hadi; , Agus Wijayanto, Ph.D; , dra.Siti Zuhriah Ariatmi. M.Hum (2013)
This study is socio-pragmatic study on Junior High School students in expressing request strategies. This study was conducted to answer the three research questions. They are (1) The strategy types used by the Students of Junior High School, (2) The contribution of social variables power, distance and gender to the choice of request. This study was a descriptive study by using qualitative approach. Subjects of this study were twenty males and twenty females of SMP N 3 students in Pati. Data for this study is elicited from the respondents through the Discourse Completion Test (DCT) which consisted of nine situations with different levels of status. The respondents in each group are then asked to write the expression of requests to complete the DCT. Their responses were collected to be analyzed based on the 8-level Trosborg's categories, the 8-level scale scheme to determine the types of request strategies used by the respondents to describe the contribution of power, distance and gender to the choice of request strategies. There were responses expressed by the students. The findings of the study showed that most of the respondents utilized Conventionally Indirect (hearer-oriented condition) in the form of ability/willingness/ permission, followed by Direct request in the form of imperatives, Conventionally Indirect (speaker-based condition) in the form of needs/demands, and indirect request. It was also found that the more familiar the interlocutors each other the more direct strategies the respondents applied. In conclusion the students of SMP N 3 Pati mostly used conventionally indirect strategies (hearer-oriented condition) to make requests according to the power status, social distance, and gender between the interlocutors